THOUGHT EXPERIMENT ANALYSES OF RENÉ DESCARTES’ COGITO - HERTOGB, C. P. (2023)
René Descartes’ Cogito is an example of a paradigmatic thought experiment, herald of both subjectivism and new science in Europe’s Modern Age, that seems to have escaped the attention of thought experiment philosophers. On deep analysis, the Cogito appears as universal instantiation (or modus ponens with implicit major ‘whatever has the property of thinking, exists’). The Cogito has strong rhetorical effects for it narratively generalizes from I to all human kind, and its historical and philosophical success can be explained from its concise enthymematic structure that rings true in many possible senses. We consider it a preeminent example of a thought experiment as it states the power of thinking as its very contents. From Descartes’ methodology of doubt we can conclude that, e.g., on a Wittgensteinian interpretation, the Cogito is a logical thought experiment rather than a psychological one.